Translating research evidence into youth behavioral health policy and action: using a community-engaged storyboard approach - Parnes, McKenna F.; Mehari, Merih; Sedlar, Georganna R.; Trevino, Cindy; Porter, Rachel; Walker, Sarah C. (Frontiers in Public Health, 2024)
Introduction There is nationwide shortage of child and adolescent behavioral health providers. Lack of diversity in the mental health care profession compounds workforce capacity issues, contributing to greater disparities in treatment access and engagement for youth from historically disenfranchised communities. Strategies are needed to foster cross-sector alignment to inform policy which can improve mental health care access and reduce disparities. This current case study details a specific research-practice-policy partnership strategy, storyboarding, as a method to engage community partners in Washington State to deliberate on information drawn from research on non-specialist models of child and adolescent mental health care to support the behavioral workforce expansion. Method Research evidence from a scoping literature review on non-specialist models of child and adolescent mental health care was shared via storyboards with community partners to inform policy efforts around the behavioral health workforce expansion. In Phase 1, community members with lived experience and clinical expertise contributed to the storyboard design process. In Phase 2, a broader community partner group shared their perspectives on the models of care presented in the storyboards via Qualtrics survey with open-ended questions. Listening sessions were also held with non-English speaking refugee and immigrant communities to elicit feedback on whether these models of care would meet their needs. Qualitative data was coded to explore emerging themes using a rapid deductive approach. Results Community partners shared mixed responses to models of care presented from the research literature. Immigrant and refugee communities explicitly stated these existing models would not fit their context. Regarding partnership strategy success, the smaller community partner group was engaged in the storyboard design process. The broader community interacted with and provided detailed responses to the models of care presented in the storyboards. Success was also reflected in community partners’ continued participation in the next stage of the project. Discussion Findings demonstrate how storyboarding can be effectively used to translate research evidence into accessible information to promote community partner engagement and capture community voice in policy processes. More work is needed exploring how such methods can be used to increase the use of research evidence in policy and practice spaces.